Evolution, genomics and epidemiology of Pseudomonas syringae: Challenges in Bacterial Molecular Plant Pathology. (25th November 2016) - Baltrus, David A.; McCann, Honour C.; Guttman, David S.
Summary: A remarkable shift in our understanding of plant‐pathogenic bacteria is underway. Until recently, nearly all research on phytopathogenic bacteria was focused on a small number of model strains, which provided a deep, but narrow, perspective on plant–microbe interactions. Advances in genome sequencing technologies have changed this by enabling the incorporation of much greater diversity into comparative and functional research. We are now moving beyond a typological understanding of a select collection of strains to a more generalized appreciation of the breadth and scope of plant–microbe interactions. The study of natural populations and evolution has particularly benefited from the expansion of genomic data. We are beginning to have a much deeper understanding of the natural genetic diversity, niche breadth, ecological constraints and defining characteristics of phytopathogenic species. Given this expanding genomic and ecological knowledge, we believe the time is ripe to evaluate what we know about the evolutionary dynamics of plant pathogens.